A handbook on the Jewish roots of the Christian faith - Evans, Craig A.; Mishkin, David (Hendrickson Publishers, 2019)
Part I. The soil -- 1. God's plan for Israel -- 2. God's plan for the nations -- 3. Messianic prophecies -- 4. Appointed times -- 5. Tabernacle and Temple -- Part II. The roots -- 6. The Jewish world of Jesus -- 7. The Jewish life and identity of Jesus -- 8. The Jewish teachings of Jesus -- Part III. The trunk -- 9. The Jewish disciples -- 10. The Jewish Paul -- 11. The Jewish message: resurrection -- Part IV. The branches -- 12. The parting ways -- 13. The mending of the ways.